1986
DOI: 10.1300/j010v11n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Failures in an Emergency Residential Alternative to Psychiatric Hospitalization

Abstract: Consecutive patient failures in an emergency residential alternative to psychiatric hospitalization are studied. Failure is defined as transfer from the alternative program to hospital inpatient care. Discriminant function analysis is employed to differentiate the failures from a sample of patients who were maintained and treated in the alternative program. The perceptions of the emergency housing program staff about the failures augment quantified results. Findings suggest that the failures can be distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Firstly, only three relate to alternatives that are purely short-term acute home treatment teams – most are hybrid services delivering both acute and continuing care [ 12 - 14 ]. Secondly, almost half the papers did not involve a multivariate analysis, so that factors independently associated with admission when others are adjusted for could not be identified [ 12 , 13 , 15 - 17 ]. Thirdly four papers had samples of fewer than 100 subjects [[ 12 , 13 , 15 ], and [ 18 ]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, only three relate to alternatives that are purely short-term acute home treatment teams – most are hybrid services delivering both acute and continuing care [ 12 - 14 ]. Secondly, almost half the papers did not involve a multivariate analysis, so that factors independently associated with admission when others are adjusted for could not be identified [ 12 , 13 , 15 - 17 ]. Thirdly four papers had samples of fewer than 100 subjects [[ 12 , 13 , 15 ], and [ 18 ]].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, almost half the papers did not involve a multivariate analysis, so that factors independently associated with admission when others are adjusted for could not be identified [ 12 , 13 , 15 - 17 ]. Thirdly four papers had samples of fewer than 100 subjects [[ 12 , 13 , 15 ], and [ 18 ]]. Finally, the candidate variables investigated differed considerably from one study to another, with none investigating anything close to a full set of candidate variables.…”
Section: Introductionmentioning
confidence: 99%
“…Because one study found that outcome is related to client diagnosis (Walsh, 1986), and another that staff's interpretations of clients' behavior was strongly influenced by the client's diagnosis (Baldwin, 1998), we evaluated whether the managers included client diagnosis and history in their narratives of good and poor outcomes. The managers did not consistently relate diagnosis and presenting symptom severity to outcome.…”
Section: Descriptions Of Good and Poor Client Outcomesmentioning
confidence: 99%
“…Often, these clients' aversive reactions to getting help initially take the form of substance abuse (about 80% of severely mentally ill patients have substance abuse problems [Drake, Teague, & Warren, 1990;Walsh, 1986]). One policy that helps clients regulate their motives for substance abuse is to require that they be on the premises of the unit, with the exception of therapy appointments and brief breaks (e.g., for smoking), for 7 days after admission.…”
Section: Understanding Clients' Aversive Reactionsmentioning
confidence: 99%
“…One of Daniella's aversive reactions took the not uncommon form of a drug relapse that necessitated her discharge from the program (e.g., Walsh, 1986). She was 60-years-old, feeble and disorganized, and had been helped off the streets and into the residential program by a diligent outreach team.…”
Section: Understanding Clients' Aversive Reactionsmentioning
confidence: 99%